Prognostic value of myocardial bridging versus non-obstructive CAD: a long-term follow-up study - Zengfa Huang; Beibei Cao; Yang Yang; Yi Ding; Xinyu Du; Wanpeng Wang; Mei Li; Zuoqin Li; Xi Wang; Xu Zhao; Xiang Wang (Scientific Reports)
Abstract We aim to investigate if myocardial bridging (MB) provides predictive value beyond its association with non-obstructive coronary artery disease (CAD) burden in a long-term follow-up and multicenter study. This study included 4176 consecutive patients with suspected CAD underwent coronary computed tomography angiography (CTA) at two hospitals in Wuhan, China, between September 2016 and December 2017 for finial analysis. Kaplan-Meier method was used to estimate the cumulative event-free survival of non-obstructive CAD burden and MB burden classifications, respectively. Further, cox regression models were applied to calculate hazard ratios (HR) for increasing non-obstructive CAD and MB burden classifications. In total, during the 6.04 years (interquartile range 5.73–6.32) follow-up, 276 (6.61%) patients occurred main adverse cardiovascular events (MACE). MB was found in 44% of patients without CAD and in 40.5% of those with non-obstructive CAD. The annualized MACE rate was 1.07 (95% confidence interval (CI): 0.92–1.24) for the no MB group and 1.13 (95% CI: 0.95–1.34) for the MB group. Univarite and Multivariate Cox regression showed that neither the depth nor the length of MB was associated with the risk of MACE. However, after adjusting with sex, age, smoke, drink, hypertension and diabetes, 2-vessel non-obstructive CAD and 3-vessel non-obstructive CAD showed significant association with the risk of MACE, with HR of 1.53 (95% CI: 1.06–2.21, P = 0.023) and 1.93 (95% CI: 1.32–2.82, P = 0.001), respectively, using no CAD as the reference group. Non-obstructive CAD, not presence of MB, is the main predictor of risk for future MACE in patients without obstructive CAD. Prospective registries in the future should include validated quality of life measures and CT-FFR with long-term outcomes to enhance the understanding of symptomatic burden and functional assessment in MB risk stratification.